2017
DOI: 10.2337/dci17-0026
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Hypertension: A Position Statement by the American Diabetes Association

Abstract: Background The aims of this study were to investigate the effects of age, gender, body mass index (BMI), glycaemic control, socioeconomic status, dyslipidaemia, hypertension, ischaemic heart disease (IHD) and smoking status in type 2 diabetes in a population-based analysis. Methods Data were collected from 46 General Practice databases in 2009 and 2014. Cox regressions were run in the non-diabetes population plus type 2 diabetes patients. Results People with type 2 diabetes (n=16,643) had higher mortality rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
391
10
40

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 563 publications
(455 citation statements)
references
References 139 publications
(44 reference statements)
14
391
10
40
Order By: Relevance
“…Moreover, numerous studies have shown that antihypertensive therapy reduces ASCVD events, heart failure, and microvascular complications. Please refer to the American Diabetes Association (ADA) position statement "Diabetes and Hypertension" for a detailed review of the epidemiology, diagnosis, and treatment of hypertension (5).…”
Section: Hypertension/blood Pressure Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, numerous studies have shown that antihypertensive therapy reduces ASCVD events, heart failure, and microvascular complications. Please refer to the American Diabetes Association (ADA) position statement "Diabetes and Hypertension" for a detailed review of the epidemiology, diagnosis, and treatment of hypertension (5).…”
Section: Hypertension/blood Pressure Controlmentioning
confidence: 99%
“…Orthostatic blood pressure measurements should be checked on initial visit and as indicated. Home blood pressure self-monitoring and 24-h ambulatory blood pressure monitoring may provide evidence of white coat hypertension, masked hypertension, or other discrepancies between office and "true" blood pressure (5). In addition to confirming or refuting a diagnosis of hypertension, home blood pressure assessment may be useful to monitor antihypertensive treatment.…”
Section: Screening and Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…3 In 2017, the American College of Cardiology (ACC)/American Heart Association (AHA) published the new guideline for hypertension, 2 and the American Diabetes Association (ADA) also published a position statement for hypertension and diabetes mellitus. 4 The ACC/AHA recommended 130/80 mm Hg as the blood pressure (BP) threshold to define hypertension, whereas the ADA recommended 140/90 mm Hg. The authors of the ADA position statement emphasized the importance of an individualized approach to treat hypertension in patients with diabetes mellitus rather than changing the BP threshold.…”
mentioning
confidence: 99%